1982
DOI: 10.1128/aem.44.6.1389-1394.1982
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of viruses from vegetable surfaces

Abstract: The efficiency of a system developed for the recovery of viruses contaminating large quantities of vegetables was investigated in the laboratory and tested in the field. Viruses seeded onto a number of leafy vegetables in the laboratory were eluted with a phosphate-buffered saline solution (pH 9.0). The eluate was clarified by glass wool filtration, and any viruses present were concentrated by adsorption to a Filterite pleated cartridge filter, eluted with 3% beef extract (pH 9.0), and further concentrated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…Such survival data are important in determining the risks of exposure over time following the contamination of produce and its subsequent storage. The recovery efficiency of 56.5 % for Ad2 from lettuce was comparable to the 55 % of enteric adenovirus type 6 recovered from lettuce by Ward et al (1982) in a previous study; nevertheless, our recovery of Ad2 from strawberries and raspberries was lower than those reported for enteric viruses (*50 %) in other studies (Bidawid et al 2000;Le Guyader et al 2004;Butot et al 2007). For example, Bidawid et al (2000) reported a recovery of 81 % of hepatitis A virus from strawberries; however, they used immunomagnetic beads and positively charged Virosorb 1MDS filters to assist in virus capture and concentration.…”
Section: Sd Standard Deviationsupporting
confidence: 82%
See 1 more Smart Citation
“…Such survival data are important in determining the risks of exposure over time following the contamination of produce and its subsequent storage. The recovery efficiency of 56.5 % for Ad2 from lettuce was comparable to the 55 % of enteric adenovirus type 6 recovered from lettuce by Ward et al (1982) in a previous study; nevertheless, our recovery of Ad2 from strawberries and raspberries was lower than those reported for enteric viruses (*50 %) in other studies (Bidawid et al 2000;Le Guyader et al 2004;Butot et al 2007). For example, Bidawid et al (2000) reported a recovery of 81 % of hepatitis A virus from strawberries; however, they used immunomagnetic beads and positively charged Virosorb 1MDS filters to assist in virus capture and concentration.…”
Section: Sd Standard Deviationsupporting
confidence: 82%
“…PV1 was recovered with an efficiency of 76.7 % from lettuce in this study. This is greater than the 58 % recovery efficiency reported by Ward et al (1982). In contrast, the recovery of PV1 from strawberries was only 0.06 %, demonstrating that virus recoveries from different types of produce can vary significantly.…”
Section: Sd Standard Deviationmentioning
confidence: 59%
“…Previous studies that involved hepatitis A virus (HAV) and poliovirus recovery from fruits and vegetables showed variable efficiencies, suggesting that the detachment process is a net result of complex virus particle-surface interactions (14,27). Studies by Legitt et al (14) and Ward et al (27) used a high pH (9.0) buffer wash to recover viruses from lettuce.…”
Section: Discussionmentioning
confidence: 99%
“…Waterborne viruses are responsible for numerous human diseases. As a consequence, the processes governing the fate, stability, and the transmission patterns of waterborne viruses in natural and in engineered systems has received considerable research attention. Among these processes is the adsorption of viruses to solid surfaces in contact with water. ,, Depending on the systems studied, these surfaces include minerals, , dissolved and particulate natural organic matter, filter membranes, and vegetables and fruit skins , as well as human skin. …”
Section: Introductionmentioning
confidence: 99%